Ageing Deep-Sea Black Coral Bathypathes patula - Marriott, Peter; Tracey, Dianne Margaret; Bostock, Helen; Hitt, Nicholas; Fallon, Stewart J. (Frontiers in Marine Science, 2020)
Deep-sea corals are a highly diverse group of marine organisms, several of which are characterised by slow growth and extreme longevity up to thousands of years. Due to their fragile forms, skeletal composition, and location, they are vulnerable to various anthropogenic threats, with some groups expected to have little to no ability to recover. Within the New Zealand region an understanding of age and growth parameters and recovery potential for some deep-sea coral fauna is being developed, but a limited understanding remains for some of the key Antipatharian black coral fauna. Ten individual colonies of the black coral species Bathypathes patula were sourced from the National Institute of Water and Atmospheric Research Invertebrate Collection for the purposes of this age estimation study. Corals were selected based on their size, completeness of the colony (whole colony from base to tip), and the regional water mass within which they grew. Coral samples from the Chatham Rise, east of New Zealand, and the Bay of Plenty, north-eastern New Zealand, were selected as the water masses for these two regions are reasonably well understood. Thin section preparations of the main stem of the 10 specimens of B. patula were observed with compound microscopes. Two interpretation protocols were used to describe the zone structures observed, both the coarse wide zones and the thin fine zones, and counts were then made of these structures. Four of the specimens were also sampled for radiocarbon assay. The radiocarbon isotope (14C) age data results were used to independently verify if either of the developed zone counting protocols reflected annual periodicity. Neither method was verified, indicating zone counting protocols could not be used to generate reliable age estimates for B. patula. Twenty radiocarbon assays from four specimens were used to derive the age and growth rate estimates presented here. The radiocarbon results from this work show B. patula to be a long-lived species, attaining ages in excess of 385 years, with linear growth rates of 5.2–9.6 mm/yr, and radial growth rates ranging from 11.1 to 35.7 μm/yr. The delicate nature of these organisms along with their longevity and slow growth rates means a low resilience and low recoverability from anthropogenic activities such as fishing and mining.